Conducting Polymers for Ophthalmic Applications - Bal, Ismail; Küçük, Israfil (CRC Press, 2022)
Drug delivery into the eye is always difficult when considering the other organs and tissues. An eye is a well-protected organ by defense mechanisms including various complex structures. These barriers, which protect the eye against foreign molecules or pathogens, also prevent drug-active substances through the eye. The vast majority of conventional treatment methods are suffering from low bioavailability (i.e., rapid clearance or low penetration into tissues). Recent developments in biomedical fields ensure promising alternatives to overcome these problems. Biodegradable polymers in ocular(ophthalmic) formulations exhibit improved residence time and mucoadhesion properties. Nanotechnology advancements have the potential to revolutionize the biomedical industry. Nano-scaled drug delivery systems help to increase bioavailability by allowing the effective dose to reach deeper tissues. Additionally, the development of metal-organic framework (MOF)-based materials is exciting and has all the properties it needs to be used in biomedical applications. It has been modified to be used in drug delivery systems, including ocular systems, thanks to its adjustable pore size and high drug loading capacity. This chapter describes using of polymers and MOF-based structures in ocular applications. © 2022 Elsevier B.V., All rights reserved.